1992
DOI: 10.1002/j.1460-2075.1992.tb05344.x
|View full text |Cite
|
Sign up to set email alerts
|

A desiccation-related Elip-like gene from the resurrection plant Craterostigma plantagineum is regulated by light and ABA.

Abstract: The resurrection plant Craterostigma plantagineum tolerates an extreme loss of cellular water. Therefore this plant is being studied as model system to analyse desiccation tolerance at the molecular level. Upon dehydration, new transcripts are abundantly expressed in different tissues of the plant. One such desiccation‐related nuclear gene (dsp‐22 for desiccation stress protein) encodes a mature 21 kDa protein which accumulates in the chloroplasts. Sequence analysis indicates that dsp‐22 is closely related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
102
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(107 citation statements)
references
References 49 publications
(39 reference statements)
5
102
0
Order By: Relevance
“…Dehydration-induced pigment binding ELIP proteins may protect plastids against injury from high-light induced freeradical generation and ultraviolet radiation (Bartels et al 1992) and their induction is a common feature during dehydration of resurrection plants (Gechev et al 2013;Dinakar et al 2012). These proteins are thought to play a role in non-photochemical quenching of light energy and the protection and repair of photosystems during desiccation and appear to be an active participant in the drying induced accumulation of protective pigments in resurrection plants .…”
Section: Desiccation-tolerant Plant Evolution Functional Plant Biologymentioning
confidence: 99%
“…Dehydration-induced pigment binding ELIP proteins may protect plastids against injury from high-light induced freeradical generation and ultraviolet radiation (Bartels et al 1992) and their induction is a common feature during dehydration of resurrection plants (Gechev et al 2013;Dinakar et al 2012). These proteins are thought to play a role in non-photochemical quenching of light energy and the protection and repair of photosystems during desiccation and appear to be an active participant in the drying induced accumulation of protective pigments in resurrection plants .…”
Section: Desiccation-tolerant Plant Evolution Functional Plant Biologymentioning
confidence: 99%
“…Until recently, few studies dealt with changes in chloroplastic protein synthesis induced by osmotic stress. In Craterostigma plantagineum, a resurrection plant able to tolerate extreme dehydration, three genes preferentially expressed upon desiccation were found to encode chloroplastic desiccation stress proteins, DSP (Bartels et al, 1992;Schneider et al, 1993). Immunological studies revealed that two proteins, DSP 22 and DSP 34, were located in the thylakoids whereas the third DSP 21, weakly homologous to a LEA protein, was found in the stroma.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, ABA and light were simultaneously required for ELIP-mRNA induction [14]. Since this protein has sequence similarity with ELIP, the effect of ABA on the expression of ELIP was tested under high-light conditions.…”
Section: The Effect Of Abscisic Acid (Aba) On Inducibility Of Elip Mrnamentioning
confidence: 99%
“…Interestingly, the activation by light stress occurs via blue and ultraviolet-A light quality [8, 91. Although closely related proteins have also been found during desiccation stress in Craterostigma [14] and during light stress in the carotenoid-overproducing Dunaliellu [15], the function of ELIP is as yet unknown.Expression of these proteins during development might help to provide additional information to finally understand ELIP induction. The primary leaf of monocotyledonous species is a well-investigated model system in this respect [16] and has already provided some information on ELIP expression during greening [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation